The Composition Process of FLS3N Dance Music 'Ratapan Bumi' Through the Digital Audio Workstation Studio One 6 Approach: A Study of Creation Methodology - Martiano, Vereki; Zaidi, Ahmad; Pardi, Ari; Surayya, Yade; Alhamda Putra, Vindo (Scoring: Journal of Film Music, 2025)
This study aims to holistically analyze and describe the creation methodology utilized by composer Vic Art. in producing the accompanying music for the FLS3N (National Student Art and Literature Competition Festival) dance, Ratapan Bumi (The Earth's Lament). This dance work possesses high narrative complexity, addressing the environmental crisis issue in Riau and integrating the Riau Malay philosophy ("The Malay will not disappear from the Earth"), while simultaneously demanding strict synchronization accuracy with the vigorous Malay Silat movements. The primary focus of the research is the optimization of the Digital Audio Workstation (DAW) Studio One 6 as an integral methodological device within the entire composition process. Employing a qualitative approach with a case study method, data were collected through in-depth interviews with the Composer, observation of the DAW project workflow, and analysis of choreography documents. The results identify three methodological pillars: (1) Conversion of Narrative into the Arrangement Structure in Studio One 6, (2) Sound Design Hybridity using VSTs to blend traditional Malay timbre with the electronic spectrum, and (3) Automation Optimization to achieve dynamic expression synchronized with the movement energy. This research confirms that DAW Studio One 6 functions not only as a production tool, but rather as an essential methodological environment in translating socio-cultural issues into a state-of-the-art sonic medium.